(untitled) (Journal of Population and Development, 2023)
An increasing number of Nepali students are going abroad each year for further studies. The recent trend is more of going for further studies at the undergraduate level rather than the previous patterns of going for graduate and postgraduate research degrees. These students often take the support of educational consultancies to facilitate their recruitment for international education. Along with this, there is a parallel increment of international educational consultancies in motivating and facilitating students to go abroad for further studies. In essence, these students who take the help of such brokering agencies often go on a “student visa”. Ethnographic information acquired from the field study conducted in Kathmandu Valley is the fundamental basis of the development of this article. Interviews and observations were the main techniques through which information was collated which were later on thematically analyzed to reach the conclusions of this study. These agencies have devised various strategies to recruit and convince students about the value and significance of international education. This article also highlights that these educational consulting firms are thriving in Nepal in a liberal economic context vis-à[1]vis the unhindered power of the globalization process.